ANALISA PERHITUNGAN PROTEKSI PIPA GAS JU SUNGAI CIPUTAT STA 60 + 523 PROYEK JALAN TOL SERPONG - CINERE - Bagas Wahyu Adhi; Beni Setiyanto (Journal of Research and Technology Studies, 2022)
The construction of Jakarta Outer Ring Road (JORR) I and Jakarta Outer Ring Road (JORR) II is one solution to overcome the reduction in road performance, which is expected to reduce congestion in the Jabodetabek area and can improve the economic and social sectors in the region. One of the toll roads that will be reviewed is the Cinere–Serpong toll road where there is pipe security at JU Ciputat STA 60 + 532. The purpose is to protect the truck load facing the girder that passes through the location of the gas pipeline. With the condition of the backfill soil and a fairly heavy traffic load on it, the impact of subsidence, soil subsidence and subgrade compression may result in the pipe being overstressed and deformed. From the results of the analysis using a Long Section with a crane load of 12.6 KN/m2, the pipe displacement due to the Crane Mobilization process in terms of the Long Section is estimated in the -Y direction (Vertical) of 0.76 cm and the -X direction (Lateral) of 0.123 cm. Analysis using the Cross Section obtained a crane load of 12.6 KN/m2, the pipe displacement due to the Crane Mobilization process in terms of the Cross Section was estimated in the -Y (Vertical) direction of 0.81 cm. The axial force that occurs is 18.6717 kg/cm2 g < the maximum allowable working pressure of 50.62 kg/cm2g. In the direction of the cross section or the direction of crossing the road, there must be a concrete slab as the foundation, in an area that is known to have gas pipes, with a concrete slab specification: K-350, fc' = 29.05 Mpa, thickness = 30 cm.